2007
DOI: 10.1111/j.1365-2184.2007.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stathmin 1 expression induced by Epstein–Barr virus in human B lymphocytes

Abstract: Thus, this study suggests that Epstein-Barr virus infection induces STMN1 expression, which play a role in cell cycle progression and proliferation in the human B lymphocyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…However, its role in MDV replication and/or spreading is still unclear. Stathmin 1 (STMN1), which also plays a role in the regulation of the microtubule system, has been shown to be up-regulated in EBV-infected B lymphocytes in human as early as 7 dpi (Baik et al, 2007). In the present study, we could not detect changes in STMN1 in spleen at 7 dpi.…”
Section: Alterations In the Proteins Associated With The Cytoskeletoncontrasting
confidence: 81%
“…However, its role in MDV replication and/or spreading is still unclear. Stathmin 1 (STMN1), which also plays a role in the regulation of the microtubule system, has been shown to be up-regulated in EBV-infected B lymphocytes in human as early as 7 dpi (Baik et al, 2007). In the present study, we could not detect changes in STMN1 in spleen at 7 dpi.…”
Section: Alterations In the Proteins Associated With The Cytoskeletoncontrasting
confidence: 81%
“…In addition, expression of stathmin has been reported previously to be up-regulated in EBV-infected primary B cells and in EBV-transformed LCLs (29). Moreover, an EBV-encoded latent protein, LMP1, has been shown to mediate phosphorylation of stathmin in EBVrelated NPC by enhancing cdc2 kinase activity (30).…”
Section: Discussionmentioning
confidence: 99%
“…The infection is associated with many types of malignances (27,28). Recently, increased levels of stathmin expression have been reported in EBV-infected primary B cells and in EBV transformed lymphoblastoid cell lines (LCLs) (29). Moreover, an EBV-encoded latent protein, LMP1, was shown to increase phosphorylation of stathmin in EBV-related nasopharyngeal carcinoma (NPC) (30,31).…”
mentioning
confidence: 99%
“…The result revealed that DNA alterations were not observed in the most of tested regions [25]. We also identified that expression of STMN1 , an oncogene, was increased in early passage LCLs compared to primary B cells [26].…”
Section: Activities Of the National Biobank Of Koreamentioning
confidence: 74%